Leitora-criadora: a experiência situada na construção dramatúrgica - Freitas, Camila Maria Grazielle (2013)
This study has the purpose of investigating the term reader-creator , on the textual aspects of the dramatical works A Morte nos Olhos , A Memória Ferida and Na Outra Margem (2010) by Antonia Pereira Bezerra. In this sense, we propose an analysis of these works based on author‟s life experience as creative matter for a autofictional narrative, highlighting the relations between the autobiographical elements (LEJEUNE, 2008; DOSSE, 2009) and fictional elements in the construction of dramatic narratives. The theoretical analysis pervades the studies fields of Reception Aesthetics (ISER, 1996), memory (RICOUER, 2007) and narrative (RICOEUR, 2010), evidencing the relation between the author and the pursuit of her memories and life experiences, the matter to elaboration of writing. Then we intend thinking a reader-creator of herself, that at the same time she seeks in her memories the biographic aspects to her narrative, she converts this reality with the insertion of fictional elements from the imagination (SARTRE, 2008)